Mastering VMware Horizon 8 : an advanced guide to delivering virtual desktops and virtual apps - Oven, Peter von (Apress, 2022)
Learn all about designing, installing, configuring, and managing VMware Horizon, with a core focus on how to deliver virtual desktops using Horizon. This book allows you to follow the complete process for deploying VMware Horizon and covers the design, deployment, and management of solutions. You'll start by reviewing remote solutions, from virtual desktops to published applications, including the benefits and what the different solutions deliver. Once through the high-level technology you'll then look at the VMware Horizon solution focusing on the architecture and the components that make up the solution and how to design a production-ready environment. Other VMware EUC technologies that complement the core Horizon solution will also be incorporate into it. Armed with the knowledge of how to design a solution, you'll move onto the installation phase and start to build a test lab environment. Once your lab is installed, you'll move onto the configuration stage where you will understand how to build, configure, and optimize virtual desktops, and desktop pools ready for end-users to use. As part of this you will also look at delivering published applications with Horizon Apps. With resources built and configured you can optimize the end-user experience with Horizon clients. The final sections of the book will focus on the other complementary solutions introducing you to VMware App Volumes and VMware Dynamic Environment Manager before finishing with how to manage the solution where we will look at some advanced configuration options and troubleshooting techniques. You will: See the core components of VMware Horizon and their functionality Design and install a Horizon environment Deliver the best end-user experience Manage the deployed solution Use VMware reference architectures to create real-life scenario examples Review the minimum requirements for designing a solution.